Making tough decisions competently: Assessing the value of product portfolio planning methods, devil’s advocacy, group discussion, weighting priorities, and evidenced-based information - Villiers, R.; Woodside, Arch; Marshall, R. (Elsevier, 2016)
This study test the efficacy of using tools proposed to increase effective decision-making (DM) by executives. Rather than serving to increase competency, management literature relevant to the study includes claims that product portfolio planning methods (P3M) and other proposals to use tools designed to increase the quality of decisions actually serve to increase incompetency versus using alternative planning tools or no planning tools. However, the designs in these studies have telling framing and structural limitations. The study here proposes improvements in testing of the core proposition that specific aids are effective in increasing the quality of decisions. This study includes alternative executive problem-solving, scenario-experimental, treatments and problem-solving by 150 individuals processing information in groups of four persons or as individuals. The findings provide independent evidence that executives' use of certain decision/planning tools within specific contexts helps to increase decision quality other than P3M. The findings of prior studies receive support in that the use of P3M in all contexts in the present study contributes high decision incompetence.